The suitability of heart rate in the prediction of oxygen consumption, energy expenditure and energy requirement for the exercising horse - Coenen, Manfred (MTT, 2008)
Oxygen consumption of an animal reflects the oxydative processes to deliver energy which is not exclusively but in majority shuttled by ATP. The circulation is responsible to submit sufficient oxygen to the tissues and to respond on increased demand. Therefore heart rate must be an indicator for oxygen consumption. Based on literature data it is possible to derive a suitable model to predict oxygen consumption by heart rate and consequently energy expenditure. A major problem is to recognize anaerobic energy supply. The lactate accumulation in blood is the only parameter which reflects this metabolic segment. Taking an energy equivalent for lactate into account, it is possible to add the anaerobic part of energy expenditure to the major fraction coming from aerobic energy metabolism. A still unsolved problem in any system for estimating energy expenditure is the change in basal metabolic rate in trained vs. untrained individuals and, even more important, the needs for restoration. Regardless of these shortages the heart rate as a predictor of energy expenditure seems to be more applicable to the exercising horse in the field as it reflects any energy relevant influence from the environment. The classic approach by setting speed as an independent variable is insensitive in that point. Using utilization ratios the energy expenditure can be converted to digestible energy or other systems to express requirements. Taking energy expenditure for metabolizable energy seems to be the most promising step.
Keywords: Ko; horse; exercise; heart rate; oxygen consumption; energy expenditure